A randomized double‐blind placebo‐controlled crossover‐style trial of buspirone in functional dysphagia and ineffective esophageal motility. Issue 2 (8th September 2017) - Aggarwal, Nitin; Thota, Prashanthi Nagavenkata; Lopez, Rocio; Gabbard, Scott
Abstract: Background: Studies suggest that Ineffective Esophageal Motility (IEM) is the manometric correlate of Functional Dysphagia (FD). Currently, there is no accepted therapy for either condition. Buspirone is a serotonin modulating medication and has been shown to augment esophageal peristaltic amplitude in healthy volunteers. We aimed to determine if buspirone improves manometric parameters and symptoms in patients with overlapping IEM/FD. Methods: We performed a prospective, double‐blind, placebo‐controlled, crossover‐style trial of 10 patients with IEM/FD. The study consisted of two 2‐week treatment arms with a 2‐week washout period. Outcomes measured at baseline, end of week 2, and week 6 include high resolution esophageal manometry (HREM), the Mayo Dysphagia Questionnaire‐14 (MDQ‐14), and the GERD‐HRQL. Results: The mean age of our 10 patients was 53 ± 9 years and 70% were female. After treatment with buspirone, 30% of patients had normalization of IEM on manometry; however, there was 30% normalization in the placebo group as well. Comparing buspirone to placebo, there was no statistically significant difference in the HREM parameters measured. There was also no statistically significant difference in symptom outcomes for buspirone compared to placebo. Of note, patients had a statistically significant decrease in the total GERD‐HRQL total score when treated with placebo compared to baseline levels. Discussion: Despite previous data demonstrating improved esophageal motility in healthy volunteers, our study shows no difference in terms of HREM parameters or symptom scores in IEM/FD patients treated with buspirone compared to placebo. Further research is necessary to identify novel agents for this condition. Abstract : Functional Dysphagia and Ineffective Esophageal Motility are poorly understood and their treatment is unclear. Expert opinion suggests the use of buspirone, but our randomized, double‐blind, placebo‐controlled, crossover‐style trial indicates that buspirone has limited utility in these conditions. More research is necessary to understand treatment options in these conditions. View the podcast on this paper at the following sites: iTunes:https://itunes.apple.com/us/podcast/id1332612017 Youtube:https://youtu.be/sZYnS6xF0jE